A revised Tesla Turbine Concept for ORC applications. (September 2017) - Manfrida, Giampaolo; Pacini, Leonardo; Talluri, Lorenzo
Abstract: The TESLA turbine is an original expander working on the principle of torque transmission by wall shear stress. The principle – demonstrated for air expanders at lab scale - has some attractive features when applied to ORC expanders: it is suitable for handling limited flow rates (as is the case for machines in the range from 500W to 5 kW), it can be developed to a reasonable size (rotor of 0.1 to 0.3 m diameters), with possible rotational speeds (which range from 1000 to 12000 rpm). The original concept was revisited, improving the stator layout (which is the main responsible for poor performance) and developing a modular design allowing to cover a wide power range, as well as a perfectly sealed operation and other fluid dynamics improvements. The flow model was developed using complete real fluid assumptions, and includes several new concepts such as bladed channels for the stator and detailed treatment of losses. Preliminary design sketches are presented and results discussed and evaluated.